Association among financial toxicity, depression and fear of cancer recurrence in young breast cancer patient-family caregiver dyads: an actor-partner interdependence mediation model - Tianye Yang; Zhu Zhu; Jianjun Shi; Lingling Tong; Jia Yang; Songli Mei; Hui Ren (BMC Psychiatry)
Abstract Purpose This study aimed to investigate the depression situation and the mediating role of fear of cancer recurrence (FCR) in the relationship between financial toxicity and depression in young breast cancer (BC) patient-family caregiver dyads. Methods A total of 196 young BC patient-family caregiver dyads at four hospitals in China were investigated. The Comprehensive scores for financial toxicity based on patient-reported outcome measures, the Hospital Anxiety and Depression Scale, and the FCR Inventory Short Form were assessed. The actor-partner interdependence mediation model using structural equation modelling in AMOS software was applied to examine the direct and indirect effects. Results In this study, there were 196 pairs of patients and family caregivers. The findings indicated a significant correlation between financial toxicity and FCR in both young BC patients and their family caregivers. Two significant partner effects were observed: the family caregiver’s financial toxicity significantly influenced the patient’s FCR (β=-0.450, P < 0.001), and the patient’s FCR influenced the family caregiver’s depression (β = 0.570, P < 0.001). Furthermore, financial toxicity in both young BC patients and family caregivers markedly affected both the actor and partner effects on dyadic depression, primarily through the patients’ FCR. Conclusions Depression in young BC patients was affected not only by themselves but also by their family caregivers. Emphasis should be placed on the interplay between financial toxicity and FCR of patients and family caregivers, with the aim of improving depression for young BC patients. Clinical implications The study emphasized the importance of addressing the experiences of both patient and family caregivers in clinical interventions. By demonstrating how financial toxicity and FCR are interlinked with depression in both parties, the study supports the development of we offer empirical support for developing comprehensive intervention strategies to alleviate mental distress and enhance mental health for patients and family caregivers.